Analysis of Physical Literacy Knowledge in Physical Education Learning of Junior High School Students 1 Pattallassang, Gowa Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The abstract contains a brief description of the purpose: The purpose of this study is to determine the level of physical literacy knowledge in physical education learning of SMP Negeri 1 Pattallassang, Gowa Regency. The sample in this study was 38 students of SMP Negeri 1 Pattallassang. The sample determination technique is by using random sampling techniques. The data analysis technique used was frequency descriptive analysis.  The results of the study show that the knowledge of physical literacy in physical education learning of students of SMP Negeri 1 Pattallassang, Gowa Regency, is classified as "High". It is illustrated from the indicators and sub-indicators of the statement in the percentage value (%) of each indicator. Motivation 84% in the "Very High" category, 55% confident in the "quite high" category, 66% in the "high" category and 76% in the "high" category. So cumulatively, the percentage value can be calculated with an average score of 68% or in the "high" category.